-2(p-10)+11=5

Simple and best practice solution for -2(p-10)+11=5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(p-10)+11=5 equation:


Simplifying
-2(p + -10) + 11 = 5

Reorder the terms:
-2(-10 + p) + 11 = 5
(-10 * -2 + p * -2) + 11 = 5
(20 + -2p) + 11 = 5

Reorder the terms:
20 + 11 + -2p = 5

Combine like terms: 20 + 11 = 31
31 + -2p = 5

Solving
31 + -2p = 5

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-31' to each side of the equation.
31 + -31 + -2p = 5 + -31

Combine like terms: 31 + -31 = 0
0 + -2p = 5 + -31
-2p = 5 + -31

Combine like terms: 5 + -31 = -26
-2p = -26

Divide each side by '-2'.
p = 13

Simplifying
p = 13

See similar equations:

| (x^2+8x)+16=25 | | 2(3x+4)=-16 | | -3d+-d=-20 | | 21k^3-18k^2+7k-6=0 | | 6x^3+15x^2-16x-40=0 | | -10+11u=2+8u | | 2y+-7=19 | | -(-5n+7)-1=2(n+5) | | -6m+18=-8m-20 | | -2=m-16/-1 | | (-0.2)(-0.58)= | | (x+5)(6x-7)=0 | | 7(7x+6)-x=8(4+6x) | | 3k=2k-16 | | f(x)=(2x-1)(x+2)(x+3) | | (7x-1)(x-7)=0 | | -4(w-7)=-7w+19 | | 18=3(j-13) | | 2(4+7x)=-3(1-4x)+5 | | 2u+38=7(u-1) | | r-10/3=3 | | .42/7.00=x/100 | | (2x-1)(2x+7)=0 | | 3(p-13)+4=13 | | x^5-ax^2-ax+1=0 | | -6(8v-4)=6(6v+4) | | n+9=4v-6 | | 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x | | (3i+8)(6i-7)= |

Equations solver categories